2005
DOI: 10.1074/jbc.m411713200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pattern of Expression and Sugar Regulation of Arabidopsis thaliana ADP-glucose Pyrophosphorylase-encoding Genes

Abstract: ADP-glucose pyrophoshorylase (ADP-Glc PPase) catalyzes the first and limiting step in starch biosynthesis. In plants, the enzyme is composed of two types of subunits (small and large) and is allosterically regulated by 3-phosphoglycerate and phosphate. The pattern of expression and sugar regulation of the six Arabidopsis thaliana ADP-Glc PPase-encoding genes (two small subunits, ApS1 and ApS2; and four large subunits, ApL1-ApL4) has been studied. Based on mRNA expression, ApS1 is the main small subunit or cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
105
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 41 publications
8
105
0
1
Order By: Relevance
“…However, ApS1 showed a sucrose-insensitive expression pattern under normal physiological conditions when mature A. thaliana plants were irrigated with sucrose-containing Murashige and Skoog medium, whereas ApL3 was induced by irrigation with the sucrose-containing medium (Crevillén et al, 2005). These observations suggest that the sucrosemediated regulation mechanism for the expression of the small subunit gene may be different from that for the large subunit gene.…”
Section: Effects Of Atwrky20 and Asml2 On The Expressionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, ApS1 showed a sucrose-insensitive expression pattern under normal physiological conditions when mature A. thaliana plants were irrigated with sucrose-containing Murashige and Skoog medium, whereas ApL3 was induced by irrigation with the sucrose-containing medium (Crevillén et al, 2005). These observations suggest that the sucrosemediated regulation mechanism for the expression of the small subunit gene may be different from that for the large subunit gene.…”
Section: Effects Of Atwrky20 and Asml2 On The Expressionmentioning
confidence: 88%
“…Each subunit is encoded by a different gene. Six genes encode proteins with homology to AGPase in the Arabidopsis thaliana genome (Crevillén et al, 2005). Two of these genes encode small subunits, ApS1 (locus number At5g48300) and ApS2 (locus number At1g05610), and the other four encode large subunits, ApL1 to ApL4 (locus numbers At5g19220, At1g27680, At4g39210, and At2g21590, respectively).…”
mentioning
confidence: 99%
“…On the contrary, the expressions of LS genes are usually tissue-and development-specific. The expression patterns and regulatory properties of different LS isoforms have been comprehensively studied in tomato (Park and Chung 1998), Arabidopsis (Crevillén et al 2003(Crevillén et al , 2005, and rice , and the results of those studies strongly indicate that AGPase heterotetramers formed in different tissues or organs display distinct kinetic and regulatory properties to control starch biosynthesis. It is suggested that the LSs of agriculturally important crops such as potato and tomato, which have undergone significant selection under both domestication and natural selection, may have evolved novel modulatory characteristics (Petreikov et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In plants and green algae, the presence of two types of subunits expanded the sequence space to explore new roles. Recently, it was shown that L subunit isoforms from Arabidopsis had different properties based on the tissue expression (2,10). On the other hand, the presence of two types of subunits may have constrained each subunit to adopt complementary roles.…”
mentioning
confidence: 99%